“ECOTOURISM: A NEW PATH TO SUSTAINABLE DEVELOPMENT AND ENVIRONMENTAL PROTECTION” (Лучшие интеллектуальные исследования, 2025)
This article provides a comprehensive analysis of ecotourism as a sustainable development strategy that balances tourism growth with environmental conservation. It examines the principles and practices of ecotourism, emphasizing responsible travel to natural areas that minimizes environmental impact and supports the preservation of ecosystems. The article explores the socio-economic benefits of ecotourism, including community empowerment, cultural preservation, and generation of alternative income sources for rural populations. It highlights the current status and potential of ecotourism in Uzbekistan, identifying key natural sites suitable for eco-friendly tourism activities. Furthermore, the article discusses the challenges faced in implementing ecotourism, such as limited infrastructure, lack of public awareness, and the need for regulatory frameworks. Practical recommendations are offered for policymakers, businesses, and local communities to promote ecotourism development through sustainable practices, environmental education, and investment in green infrastructure.